Study of seismic activity in the Haiyuan-Liupanshan region using automated microseismic detection techniques - MengYa Li; YiJian Zhou; XianWei Zeng; ChenXi Wang; JiaWei He (Geomatics, Natural Hazards & Risk, 2024)
Using continuous waveform data from 27 fixed seismic stations in Ningxia spanning nearly a decade from 2013 to September 2022, the automatic detection matching method (PALM) was employed to capture 34,373 seismic events across the region, which is twelve times more than manual cataloging during the same period. The events were used as a template to search for smaller seismic events in the Haiyuan-Liupanshan region. After location, a total of 14,741 microseismic events were detected. Based on this expanded dataset, we calculated b value and analysis the depth profiles of seismic. The findings indicate that the distribution of microseismicity has characteristics of zonation, clustering and interruption. Seismic activity aligns with active faults and closely correlates with tectonic zones. The areas with seismic gaps and low b-value zones indicate a higher stress level on the north side of the middle section of the Haiyuan Fault, which was also the epicenter of the magnitude 4.9 Pingchuan earthquake on December 31, 2023. The seismic profiles show that the regional earthquakes mainly occur at a depth of more than 30 km. The depth distribution of these earthquakes reflects the inclination of the fault and thus corresponds exactly to the actual conditions.